Di-ureasil xerogels containing lithium bis(trifluoromethanesulfonyl)imide for application in solid-state electrochromic devices - Barbosa, Paula C. (2009)
In this study we report the characterization of a solid-state electrochromic device based on poly(ethylene oxide) (PEO)/siloxane hybrid networks doped with lithium bis(trifluoromethanesulfonyl)imide (LiTFSI). The polymer networks prepared, classed as di-ureasils and represented by d-U(2000), were produced by the sol-gel process and are composed of a siliceous framework to which polyether chains containing 40.5 oxyethylene repeating units are covalently bonded through urea linkages. Samples with compositions of 200 ≥ n ≥ 0.5 (where n is the molar ratio (OCH2CH2)/Li+)) were characterized by thermal analysis and complex impedance measurements, cyclic voltammetry at a gold microelectrode. Finally, we report the results of preliminary evaluation of these polymer electrolytes as components in prototype electrochromic devices. Electrochromic parameters such as coloration efficiency, optical contrast and stability were also evaluated. The devices exhibit open-circuit memory and stable electrochromic performances.